2021
DOI: 10.3390/ma14081829
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Iron Ore Tailing as Cementitious Material for Eco-Friendly Design of Ultra-High Performance Concrete (UHPC)

Abstract: In this research, iron ore tailing (IOT) is utilized as the cementitious material to develop an eco-friendly ultra-high performance concrete (UHPC). The UHPC mix is obtained according to the modified Andreasen and Andersen (MAA) packing model, and the applied dosage of IOT is 10%, 20%, and 30% (by weight), respectively. The calculated packing density of different mixtures is consistent with each other. Afterwards, the fresh and hardened performance of UHPC mixtures with IOT are evaluated. The results demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Cheng et al (2016) found that IOTs after mechanical activation had pozzolanic activity and could be used as SCM for concrete. Ling et al (2021) used IOTs as the CCM to prepare environment friendly ultra-high performance concrete (UHPC), which facilitated the development of long-term compressive strength and the improvement of pore structure, thus ensuring the durability of UHPC. Cheng et al (2020) prepared concrete with strong permeability resistance and good freeze-thaw resistance by replacing part of OPC with IOTs after mechanical grinding.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2016) found that IOTs after mechanical activation had pozzolanic activity and could be used as SCM for concrete. Ling et al (2021) used IOTs as the CCM to prepare environment friendly ultra-high performance concrete (UHPC), which facilitated the development of long-term compressive strength and the improvement of pore structure, thus ensuring the durability of UHPC. Cheng et al (2020) prepared concrete with strong permeability resistance and good freeze-thaw resistance by replacing part of OPC with IOTs after mechanical grinding.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have studied the mechanical properties of concrete prepared by iron tailing sand, and there are many reports on the preparation of high-performance concrete by iron tailing powder [9][10][11]. However, there are few studies on freeze-thaw properties of iron tailings concrete and few reports on the prediction of freeze-thaw resistance of iron tailings concrete [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al, investigated the effect of curing conditions on the mechanical and microstructural properties of ultra-high-performance concrete incorporating iron tailing powder and found that the strength of concrete first increased and then decreased with the increase in iron tailing powder dosing [ 16 ]. Ling et al, conducted an environmental design study of ultra-high performance concrete using iron ore tailings as cement material and found that iron tailings promote optimization of long-term compressive strength and pore structure of concrete [ 17 ]. Another study on the influence of iron ore tailings concrete by working environmental conditions has been explored by several scholars, one after another.…”
Section: Introductionmentioning
confidence: 99%